Olefin epoxidized titanium silicon oxide catalyst as well as preparation method and application thereof
Through a simple and green preparation method, an olefin titanium silicon catalyst with high catalytic properties is prepared, which solves the problems of poor performance and complex preparation of existing catalysts, and achieves a highly efficient and stable olefin epoxidation reaction.
Patent Information
- Application Number
- CN202311269544.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-28
AI Technical Summary
The existing olefin titanium silicon epoxide catalysts have poor catalytic performance, complex preparation process, and require the use of reagents with strong corrosiveness and high environmental hazards.
The titanium-containing binder is prepared by mixing the silicon source, titanium source, organic alkali and water and hydrothermal treatment, then kneading with the silicon source and pore-forming agent and baking, and finally mixing with the organic silane and the organic amine to produce an olefin epoxide titanium silicon catalyst with high catalytic properties.
This catalyst has high conversion rate, high epoxide selectivity, good catalytic stability in the olefin epoxidation reaction, and simple and green preparation method, reducing environmental hazards.
Smart Images

Figure CN119702067A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of petrochemical catalysts, and in particular relates to an olefin epoxidation titanium silicon catalyst and a preparation method and application thereof. Background Art
[0002] Epoxides are important organic chemical raw materials, mainly used in the production of diols, polyesters, polyether polyols, etc. Its varieties mainly include ethylene oxide, propylene oxide, 1,2-epoxypentane and 1,2-epoxyhexane. At present, epoxides are basically produced by selective oxidation of olefins. For example, ethylene oxide is obtained by epoxidation of ethylene and air under the action of a silver catalyst; the industrial production method of 1,2-epoxypentane and 1,2-epoxyhexane is the 1-pentene and 1-hexene organic peroxy acid oxidation method, which has problems such as severe equipment corrosion, high risk factor, and poor atomic economy; the industrial production routes of propylene oxide mainly include the chlorohydrin method, the co-oxidation method with co-products (PO / SM method and PO / MTBE method or PO / TBA method), the hydrogen peroxide method without co-products (HPPO method) and the cumene hydroperoxide method (CHP method). The chlorohydrin process is gradually being phased out due to serious environmental pollution. The co-oxidation process with by-products overcomes the shortcomings of the chlorohydrin process, such as pollution and corrosion. However, the process is long, the investment is large, the output of by-products is large, and the market demand has a great impact on the process. The CHP process and HPPO process without by-products have become the development direction of propylene oxide production technology due to their low pollution and no by-product generation. The core of these two technologies is the propylene epoxidation catalyst used therein.
[0003] Titanium silicon materials have good catalytic activity for the selective oxidation of hydrocarbons and can be used to catalyze the epoxidation of olefins to prepare epoxides. US4410501 first disclosed the synthesis method of TS-1 molecular sieve. First, a titanium-containing colloidal solution was prepared using an aqueous solution of tetrapropylammonium hydroxide, organic titanate and organic silicate as raw materials, and then synthesized by direct hydrothermal crystallization. The invention of this new catalytic material has laid the foundation for the research on efficient hydrocarbon oxidation reactions and the development of environmentally friendly processes. However, since TS-1 is a microporous molecular sieve with an MFI structure, it is limited to being used for the oxidation of hydrocarbons with hydrogen peroxide (H 2 O 2 ) is used as the oxidant to catalyze the HPPO process of preparing propylene oxide by oxidizing propylene. When organic peroxides such as cumene hydroperoxide (CHP) and ethylbenzene hydroperoxide (EBHP) are used as the oxidant, TS-1 has almost no catalytic activity.
[0004] US3923843 and US4367342 disclose that EBHP can selectively oxidize propylene to propylene oxide using titanium-containing amorphous silica as a catalyst. However, due to the small specific surface area and pore volume of the amorphous silica carrier used, the low titanium loading, and the strong hydrophilicity of the catalyst surface, the catalytic activity is low, and the reaction product propylene oxide is easily hydrolyzed by ring opening on its surface, and further polymerized to form a polymer with a larger molecular weight and attached to the catalyst surface, which not only affects the selectivity of the catalyst for propylene oxide, but also easily causes the catalyst to deactivate and reduce the stability of the catalyst. Therefore, this type of catalyst is difficult to be competent for a long-term and low-consumption high-efficiency propylene catalytic epoxidation reaction system.
[0005] CN1500004A and CN1248579A disclose that a catalyst having a structure similar to Ti-MCM-41 can selectively oxidize propylene to propylene oxide by using CHP or EBHP as an oxidant. However, since the quaternary ammonium salt template used in the synthesis process of the catalyst is expensive and requires a long crystallization process, the production efficiency of the catalyst is low, resulting in a high manufacturing cost of the catalyst; in addition, since the activity and hydrophobicity of the catalyst are not ideal, there are many by-products and poor stability, the economic efficiency of the industrial production of propylene oxide is significantly affected.
[0006] CN107224993B TiCl 4 Loaded on a silica gel carrier containing metal salts, combined with steam washing, surface SiO 2 Coating and silanization treatment to obtain SiO with high selectivity for propylene oxide 2 -Ti-MeO-SiO 2 CN107715868B first pre-hydrolyzes the silicon source, then adds the titanium source to react to form a sol, sprays the sol into liquid ammonia after atomization to form, and then expands the pores, and then dries, roasts and silanes to obtain Ti-SiO 2 Composite oxide catalysts. These two methods have long preparation processes and require the use of titanium source TiCl which is highly corrosive and environmentally harmful. 4 Or liquid ammonia, which is not conducive to industrial production.
[0007] In general, the titanium silicon olefin epoxidation catalysts in the prior art have poor catalytic performance, complex preparation processes, and require the use of highly corrosive and environmentally hazardous reagents. Therefore, it is necessary to develop titanium silicon olefin epoxidation catalysts with good catalytic performance and simple and green preparation methods. Summary of the invention
[0008] One of the technical problems to be solved by the present invention is to solve the problems that the existing olefin epoxidation titanium silicon catalyst has poor catalytic performance, complicated preparation process, and requires the use of highly corrosive and environmentally harmful reagents, and to provide an olefin epoxidation titanium silicon catalyst. The catalyst has good catalytic performance.
[0009] The second technical problem to be solved by the present invention is to solve the problem that there is no simple and green method for preparing olefin epoxidation titanium silicon catalyst with good catalytic performance, and to provide a preparation method of olefin epoxidation titanium silicon catalyst. The preparation method has the characteristics of being simple and green.
[0010] The third technical problem to be solved by the present invention is to provide an application of an olefin epoxidation titanium silicon catalyst in an olefin epoxidation reaction. The catalyst of the present invention has the characteristics of high olefin conversion rate, high epoxide selectivity and good catalytic stability.
[0011] In order to solve one of the above technical problems, the present invention provides a titanium silicon catalyst for olefin epoxidation, wherein the ultraviolet Raman spectrum is 364±6cm -1 、500±6cm -1 and 1102±6cm -1 There are spectral peaks at 1102±6cm -1 The intensity of the peak is 364±6cm -1 1.0 to 10.0 times, preferably 3.0 to 8.0 times, the peak intensity.
[0012] According to the present invention, further, the titanium silicon catalyst comprises silicon, titanium and carbon, and the overall silicon-titanium molar ratio is 20-200, preferably 25-100.
[0013] According to the present invention, further, the titanium silicon catalyst has a surface silicon-titanium molar ratio of 10 to 100, preferably 12 to 50; and a surface silicon-carbon molar ratio of 0.5 to 6.0, preferably 1.0 to 5.0.
[0014] According to the present invention, further, the titanium silicon catalyst is at 20°C, P / P 0 =0.1 and the adsorption time is 2h. The toluene adsorption amount measured is 150-450 mg / g molecular sieve, preferably 250-400 mg / g molecular sieve.
[0015] According to the present invention, further, the mechanical strength of the titanium silicon catalyst is 40 to 90 N / cm, preferably 50 to 80 N / cm.
[0016] In order to solve the second technical problem mentioned above, the second aspect of the present invention provides a method for preparing an olefin epoxidation titanium silicon catalyst, comprising the following steps:
[0017] (1) mixing silicon source A, titanium source, organic base and water, and subjecting them to hydrothermal treatment to prepare a titanium-containing binder;
[0018] (2) kneading the silicon source B, the titanium-containing binder and the pore-forming agent prepared in step (1) into a mold, and calcining the mold to obtain a catalyst precursor;
[0019] (3) The catalyst precursor of step (2) is contacted with a mixture of an organic silane and an organic amine to obtain the titanium silicon catalyst.
[0020] According to the present invention, further, the ratio of each material in step (1) is calculated as follows in terms of molar ratio: silicon source A is SiO 2 Calculation: Titanium source is TiO 2 Calculation: organic base: water = 1: x: y: z; wherein x = 0.01-0.5, y = 0.05-0.5, z = 5-25, preferably: x = 0.05-0.3, y = 0.1-0.4, z = 12-20.
[0021] According to the present invention, further, in step (1), the silicon source A is selected from at least one of tetraethyl orthosilicate, fumed silica, and silica sol; the titanium source is selected from at least one of tetrabutyl titanate, tetraisopropyl titanate, titanium tetrachloride, hexafluorotitanic acid, and ammonium hexafluorotitanate; the organic base is selected from at least one of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, dimethyldiethylammonium hydroxide, dimethyldiisopropylammonium hydroxide, piperidine, and hexamethyleneimine. Preferably, the silicon source A is selected from at least one of tetraethyl orthosilicate and silica sol; the titanium source is selected from at least one of tetrabutyl titanate, tetraisopropyl titanate, and hexafluorotitanic acid; the organic base is selected from at least one of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, dimethyldiethylammonium hydroxide, and dimethyldiisopropylammonium hydroxide.
[0022] According to the present invention, further, the hydrothermal treatment in step (1) is carried out in stages. The conditions for the first stage hydrothermal treatment are: 60-119°C for 1-24 hours, preferably 80-100°C for 2-20 hours; the conditions for the second stage hydrothermal treatment are: 120-180°C for 0.5-6 hours, preferably 130-170°C for 2-5 hours; and / or, the temperature of the second stage hydrothermal treatment is 10-120°C higher than that of the first stage hydrothermal treatment, preferably 20-100°C.
[0023] According to the present invention, further, in step (2), the ratio of each material is such that the silicon source B is SiO 2The mass ratio of the titanium-containing binder to the pore-forming agent in step (1) is 1:0.2-1.8:0.01-0.3, preferably 1:0.3-1.5:0.05-0.2. During the kneading and molding process, a certain amount of water can be appropriately evaporated or added to ensure that the prepared catalyst has good mechanical strength.
[0024] According to the present invention, further, in step (2), the silicon source B is selected from at least one of fumed silica or silicon powder; the pore-forming agent is selected from at least one of sesbania powder, cellulose, chitosan, lignin, starch, polyethylene glycol, triblock copolymer P123, and F127.
[0025] According to the present invention, further, the calcination conditions in step (2) are: calcination at 450-650° C. in an oxygen-containing atmosphere for 4-12 hours. Drying is performed before calcination at 60-120° C. for 1-24 hours.
[0026] According to the present invention, further, in step (3), the mass ratio of the catalyst precursor to the organosilane and the organic amine is 1:0.01-0.5:0.01-0.5, preferably 1:0.05-0.40:0.05-0.40.
[0027] According to the present invention, further, the organosilane in step (3) is selected from at least one of hexamethyldisilazane, triethylchlorosilane, chloromethyl (dimethyl) methoxysilane, octadecyldimethylmethoxysilane, ethoxytrimethylsilane, triallylethoxysilane, dimethyldiethoxysilane, and methylphenyldimethoxysilane, and is preferably at least one of hexamethyldisilazane, triethylchlorosilane, and chloromethyl (dimethyl) methoxysilane; the organic amine is selected from at least one of methylamine, ethylamine, ethylenediamine, n-propylamine, n-butylamine, diethylamine, triethylamine, and hexanediamine, and is preferably at least one of methylamine, ethylamine, ethylenediamine, n-propylamine, n-butylamine, and diethylamine.
[0028] According to the present invention, further, the treatment conditions in step (3) are: 80-180°C for 0.5-24 hours, preferably: 100-160°C for 1-12 hours. After treatment, washing with an organic solvent and drying, wherein the drying conditions are 60-120°C for 1-24 hours.
[0029] The present invention also provides a titanium silicon catalyst for olefin epoxidation prepared by the method.
[0030] According to the present invention, further, the titanium silicon catalyst prepared by the method has an ultraviolet Raman spectrum at 364±6cm -1 、500±6cm -1 and 1102±6cm -1 There are spectral peaks at 1102±6cm-1 The intensity of the peak is 364±6cm -1 1.0 to 10.0 times, preferably 3.0 to 8.0 times, the peak intensity.
[0031] According to the present invention, further, the titanium silicon catalyst prepared by the method comprises silicon element, titanium element and carbon element, and the overall silicon-titanium molar ratio is 20-200, preferably 25-100.
[0032] According to the present invention, further, the titanium silicon catalyst prepared by the method has a surface silicon-titanium molar ratio of 10 to 100, preferably 12 to 50; and a surface silicon-carbon molar ratio of 0.5 to 6.0, preferably 1.0 to 5.0.
[0033] According to the present invention, further, the titanium silicon catalyst prepared by the method is at 20°C, P / P 0 =0.1 and the adsorption time is 2h. The toluene adsorption amount measured is 150-450 mg / g molecular sieve, preferably 250-400 mg / g molecular sieve.
[0034] According to the present invention, further, the titanium silicon catalyst prepared by the method has a mechanical strength of 40 to 90 N / cm, preferably 50 to 80 N / cm.
[0035] In order to solve the third of the above technical problems, the present invention provides an application of the above olefin epoxidation titanium silicon catalyst in olefin epoxidation reaction.
[0036] According to the present invention, further, the step of applying comprises: mixing olefin, alkylbenzene hydroperoxide solution and solvent as raw material liquid, and contacting and reacting with the catalyst. The reaction device is a fixed bed reactor.
[0037] According to the present invention, further, the olefin is a liquefied olefin; the olefin includes at least one selected from propylene, allyl chloride, butene, pentene, cyclopentene, hexene and cyclohexene; the alkylbenzene hydroperoxide includes at least one selected from cumene hydroperoxide and ethylbenzene hydroperoxide; the mass fraction of alkylbenzene hydroperoxide in the alkylbenzene hydroperoxide solution is 30% to 90%; the solvent is selected from at least one of cumene, ethylbenzene, toluene and benzene.
[0038] According to the present invention, further, in the raw material liquid, the molar ratio of olefin to alkylbenzene hydroperoxide is 1:0.1-0.5; the mass fraction of olefin in the raw material liquid is 5%-50%.
[0039] According to the present invention, further, the flow rate of the catalyst per unit mass of the raw material liquid is 3 to 30 mL·g cat. -1 ·h -1; The reaction temperature is 40-120°C, and the reaction pressure is 0.1-4MPa.
[0040] Compared with the prior art, the present invention has the following advantages:
[0041] 1. In the present invention, the ultraviolet Raman spectrum of the olefin epoxidation titanium silicon catalyst is at 364±6cm -1 、500±6cm -1 and 1102±6cm -1 There are spectral peaks at 1102±6cm -1 The intensity of the peak is 364±6cm -1 1 to 10 times the peak intensity. 364±6cm -1 The peaks are attributed to SiO 2 Base, 500±6cm -1 and 1102±6cm -1 The peak is attributed to the framework tetracoordinated titanium species, which is the catalytic active center for olefin epoxidation. High intensity 500±6cm -1 and 1102±6cm -1 The appearance of the spectrum peak indicates the presence of a large number of titanium species in good condition. 0 =0.1 and the adsorption time is 2h, the toluene adsorption amount measured is 150-450 mg / g molecular sieve, indicating that the catalyst has good hydrophobicity and large pore volume, which is conducive to diffusion and mass transfer. The titanium silicon catalyst is used in olefin epoxidation reaction and has the characteristics of high olefin conversion rate, high epoxide selectivity and good catalytic stability.
[0042] 2. In the present invention, the preparation method of the catalyst is to first mix silicon source A, titanium source, organic base and water, perform hydrothermal treatment to obtain a titanium-containing binder, then knead silicon source B, titanium-containing binder and pore-forming agent to form, and calcine to obtain a catalyst precursor, and finally contact the catalyst precursor with a mixture of organic silane and organic amine to obtain the titanium silicon catalyst. The preparation method of the present invention can simply and effectively introduce a skeleton tetracoordinate titanium species into the prepared titanium silicon catalyst by preparing a titanium-containing binder, kneading it with silicon source B and a pore-forming agent to form and calcine it, and further treat it with organic silane and organic amine to reduce the silicon hydroxyl group, improve the state of the skeleton tetracoordinate titanium species, and improve the hydrophobicity of the catalyst, thereby improving the catalytic performance. The titanium silicon catalyst prepared by the method of the present invention is used in the olefin epoxidation reaction and has excellent catalytic activity, selectivity and stability.
[0043] 3. The catalyst of the present invention is used in olefin epoxidation reaction, has excellent catalytic performance, high olefin conversion rate, high epoxide selectivity, good catalytic stability, and shows good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is the UV Raman spectrum of the olefin epoxidation titanium silicon catalyst prepared in [Example 1];
[0045] Figure 2 This is the UV Raman spectrum of the olefin epoxidation titanium silicon catalyst prepared in [Comparative Example 1];
[0046] Figure 3 This is the UV Raman spectrum of the olefin epoxidation titanium silicon catalyst prepared in [Comparative Example 2];
[0047] Figure 4 This is the UV Raman spectrum of the olefin epoxidation titanium silicon catalyst prepared in [Comparative Example 3];
[0048] Figure 5 This is the UV Raman spectrum of the olefin epoxidation titanium silicon catalyst prepared in [Comparative Example 4];
[0049] Figure 6 This is the UV Raman spectrum of the olefin epoxidation titanium silicon catalyst prepared in [Comparative Example 5];
[0050] Figure 7 This is the UV Raman spectrum of the olefin epoxidation titanium silicon catalyst prepared in [Comparative Example 6]. DETAILED DESCRIPTION
[0051] The technical solution of the present invention is further described below in conjunction with embodiments, but is not limited to the following embodiments.
[0052] In the present invention, unless otherwise expressly stated, percentages and percentage contents are all measured by mass. Unless otherwise expressly stated, throughout the specification and claims, the term "comprise" or its variations such as "comprises" or "comprising" etc. shall be understood to include the stated steps or components, without excluding other steps or other components.
[0053] In the present invention, including in the following embodiments and comparative examples, the titanium species state and the overall silicon-titanium molar ratio of the titanium silicon catalyst are determined by ultraviolet Raman spectroscopy and inductively coupled atomic emission spectroscopy, respectively; the surface silicon-titanium molar ratio and the surface silicon-carbon molar ratio of the titanium silicon catalyst are determined by X-ray photoelectron spectroscopy; the toluene adsorption amount and the mechanical strength of the titanium silicon catalyst are determined by benzene adsorption and a strength tester, respectively.
[0054] In the present invention, the ultraviolet Raman spectrum test method is: using a domestic UV Raman-100 ultraviolet Raman spectrometer for testing, the excitation wavelength is 244nm, the laser power irradiated on the sample is 5.0mW, and the spectral resolution is 4cm -1The intensity of a peak is obtained by subtracting the baseline background from the peak value of the peak.
[0055] In the present invention, the inductively coupled atomic emission spectrometry testing method is: using a Varian-2000 analyzer to analyze the overall silicon-titanium molar ratio in the sample, and before the test, the sample is dissolved in a hydrofluoric acid solution.
[0056] In the present invention, the X-ray photoelectron spectroscopy testing method is: using AXIS ULTRA DLD X-ray photoelectron spectrometer to measure the silicon, titanium, carbon species and signal intensity on the surface of the titanium silicon catalyst, and based on this, the surface silicon titanium molar ratio and the surface silicon carbon molar ratio are calculated.
[0057] In the present invention, the benzene adsorption test method is: using Hiden Company's intelligent weight analyzer for testing, and before the test, the sample is vacuum pretreated at 353K for 10 hours.
[0058] In the present invention, the mechanical strength test method is: use DL-2 particle strength tester to test, first test the size of the catalyst in the force direction, then measure the external force required to extrude the catalyst into powder, and divide the external force by the size to obtain the mechanical strength of the catalyst.
[0059] In the present invention, the reaction liquid after passing through the titanium silicon catalyst bed is collected, the concentration of cumene hydroperoxide in the reaction liquid is determined by iodine titration, and the residual rate of cumene hydroperoxide and the conversion rate of cumene hydroperoxide are calculated.
[0060]
[0061] Isopropylbenzene hydroperoxide conversion rate % = 1 - Isopropylbenzene hydroperoxide residual rate %.
[0062] In the present invention, gas chromatography is used to analyze the product composition, and the selectivity of the main product epoxide and the by-product diol and alcohol ether, and the main-by-product ratio are calculated.
[0063]
[0064]
[0065] In the present invention, the timing starts from when the two plunger pumps are turned on, and ends when the residual rate of cumene hydroperoxide in the reaction solution reaches 2%. The corresponding operating time is the catalyst stabilization time.
[0066] [Example 1]
[0067] (1) First, SiO 2 :TiO 2: Tetrapropylammonium hydroxide: water is 1:0.2:0.4:15. Corresponding amounts of water, tetrapropylammonium hydroxide, tetra-n-butyl titanate and ethyl orthosilicate are uniformly mixed, and then treated at 80°C for 8 hours and then at 150°C for 2 hours to obtain a titanium-containing binder.
[0068] (2) Then, the fumed silica, titanium-containing binder, and field sesbania powder are uniformly mixed in a mass ratio of 1:1:0.1, and stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100°C for 8 hours, and then calcined at 550°C for 6 hours to obtain a cylindrical catalyst precursor.
[0069] (3) The cylindrical catalyst precursor, hexamethyldisilazane and ethylenediamine were mixed in a mass ratio of 1:0.2:0.1, treated at 120°C for 8 hours, washed with ethanol and dried at 100°C for 8 hours to obtain an olefin epoxidation titanium silicon catalyst, which was recorded as S1.
[0070] The UV Raman spectrum of the catalyst S1 is as follows Figure 1 As shown, 364 cm -1 , 500cm -1 、1102cm -1 Spectral peak, 1102cm -1 The peak intensity is 364cm -1 6.0 times the peak intensity, 364cm -1 The peaks are attributed to SiO 2 Base, 500cm -1 、1102cm -1 The peaks belong to the framework tetracoordinated titanium species, which is the catalytic active center for olefin epoxidation; the overall silicon-titanium molar ratio of the catalyst S1 is 30, the surface silicon-titanium molar ratio is 15, and the surface silicon-carbon molar ratio is 3.0; the catalyst S1 is heated to 20°C and P / P 0 =0.1 and the adsorption time is 2h. The toluene adsorption amount measured is 300mg / g; the mechanical strength of the catalyst S1 is 60N / cm.
[0071] [Example 2]
[0072] (1) First, SiO 2 :TiO 2 : Tetrapropylammonium hydroxide: water is 1:0.02:0.1:10. Corresponding amounts of water, tetrapropylammonium hydroxide, tetra-n-butyl titanate and ethyl orthosilicate are uniformly mixed, then treated at 80°C for 8 hours and then at 150°C for 2 hours to obtain a titanium-containing binder.
[0073] (2) Then, the fumed silica, titanium-containing binder, and field sesbania powder are uniformly mixed in a mass ratio of 1:1:0.1, and stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100°C for 8 hours, and then calcined at 550°C for 6 hours to obtain a cylindrical catalyst precursor.
[0074] (3) The cylindrical catalyst precursor, hexamethyldisilazane and ethylenediamine were mixed in a mass ratio of 1:0.2:0.1, treated at 120°C for 8 hours, washed with ethanol and dried at 100°C for 8 hours to obtain an olefin epoxidation titanium silicon catalyst, which was recorded as S2.
[0075] The UV Raman spectrum of the catalyst S2 is Figure 1 Similarly, 370 cm -1 、494cm -1 、1108cm -1 Spectral peak, 1108cm -1 The peak intensity is 370 cm -1 The overall silicon-titanium molar ratio of the catalyst S2 is 200, the surface silicon-titanium molar ratio is 100, and the surface silicon-carbon molar ratio is 2.5; the catalyst S2 is at 20°C, P / P 0 =0.1 and the adsorption time is 2h. The toluene adsorption amount measured is 325 mg / g; the mechanical strength of the catalyst S2 is 54 N / cm.
[0076] [Example 3]
[0077] (1) First, SiO 2 :TiO 2 : Piperidine: water is 1:0.5:0.4:25. Corresponding amounts of water, piperidine, titanium tetrachloride and fumed silica are uniformly mixed, and then treated at 80°C for 8 hours and then at 150°C for 2 hours to obtain a titanium-containing binder.
[0078] (2) Then, the fumed silica, titanium-containing binder, and field sesbania powder are uniformly mixed in a mass ratio of 1:1:0.1, and stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100°C for 8 hours, and then calcined at 550°C for 6 hours to obtain a cylindrical catalyst precursor.
[0079] (3) The cylindrical catalyst precursor, hexamethyldisilazane and ethylenediamine were mixed in a mass ratio of 1:0.2:0.1, treated at 120°C for 8 hours, washed with ethanol and dried at 100°C for 8 hours to obtain an olefin epoxidation titanium silicon catalyst, which was recorded as S3.
[0080] The UV Raman spectrum of the catalyst S3 is Figure 1 Similarly, 358 cm was observed-1 、506cm -1 、1096cm -1 Spectral peak, 1096cm -1 The peak intensity is 358cm -1 The overall silicon-titanium molar ratio of the catalyst S3 is 20, the surface silicon-titanium molar ratio is 10, and the surface silicon-carbon molar ratio is 3.6; the catalyst S3 is at 20°C, P / P 0 =0.1 and the adsorption time is 2h. The toluene adsorption amount measured is 272 mg / g; the mechanical strength of the catalyst S3 is 80 N / cm.
[0081] [Example 4]
[0082] (1) First, SiO 2 :TiO 2 : Tetrabutylammonium hydroxide: water is 1:0.25:0.4:15. Corresponding amounts of water, tetrabutylammonium hydroxide, hexafluorotitanic acid and silica sol are uniformly mixed, and then treated at 80°C for 8 hours and then at 150°C for 2 hours to obtain a titanium-containing binder.
[0083] (2) Then, the fumed silica, titanium-containing binder, and field sesbania powder are uniformly mixed in a mass ratio of 1:1:0.1, and stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100°C for 8 hours, and then calcined at 550°C for 6 hours to obtain a cylindrical catalyst precursor.
[0084] (3) The cylindrical catalyst precursor, hexamethyldisilazane and ethylenediamine were mixed in a mass ratio of 1:0.2:0.1, treated at 120°C for 8 hours, washed with ethanol and dried at 100°C for 8 hours to obtain an olefin epoxidation titanium silicon catalyst, which was recorded as S4.
[0085] The UV Raman spectrum of the catalyst S4 is Figure 1 Similarly, 366 cm -1 、498cm -1 、1103cm -1 Spectral peak, 1103cm -1 The peak intensity is 366cm -1 The overall silicon-titanium molar ratio of the catalyst S4 is 28, the surface silicon-titanium molar ratio is 14, and the surface silicon-carbon molar ratio is 3.8; the catalyst S4 is at 20°C, P / P 0 =0.1 and the adsorption time is 2h. The toluene adsorption amount measured is 250 mg / g; the mechanical strength of the catalyst S4 is 76 N / cm.
[0086] [Example 5]
[0087] (1) First, SiO 2 :TiO 2 : Tetrapropylammonium hydroxide: water is 1:0.2:0.4:15. Corresponding amounts of water, tetrapropylammonium hydroxide, tetra-n-butyl titanate and ethyl orthosilicate are uniformly mixed, then treated at 60°C for 24 hours and then at 180°C for 1 hour to obtain a titanium-containing binder.
[0088] (2) Then, the fumed silica, titanium-containing binder, and field sesbania powder are uniformly mixed in a mass ratio of 1:1:0.1, and stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100°C for 8 hours, and then calcined at 550°C for 6 hours to obtain a cylindrical catalyst precursor.
[0089] (3) The cylindrical catalyst precursor, hexamethyldisilazane and ethylenediamine were mixed in a mass ratio of 1:0.2:0.1, treated at 120°C for 8 hours, washed with ethanol and dried at 100°C for 8 hours to obtain an olefin epoxidation titanium silicon catalyst, which was recorded as S5.
[0090] The UV Raman spectrum of the catalyst S5 is Figure 1 Similarly, 362 cm -1 、502cm -1 、1101cm -1 Spectral peak, 1101cm -1 The peak intensity is 362cm -1 The overall silicon-titanium molar ratio of the catalyst S5 is 36, the surface silicon-titanium molar ratio is 17, and the surface silicon-carbon molar ratio is 2.5; the catalyst S5 is at 20°C, P / P 0 =0.1 and the adsorption time is 2h. The toluene adsorption amount measured is 320 mg / g; the mechanical strength of the catalyst S5 is 64 N / cm.
[0091] [Example 6]
[0092] (1) First, SiO 2 :TiO 2 : Tetrapropylammonium hydroxide: water is 1:0.2:0.4:15. Corresponding amounts of water, tetrapropylammonium hydroxide, tetra-n-butyl titanate and ethyl orthosilicate are uniformly mixed, and then treated at 110°C for 1 hour and then at 120°C for 6 hours to obtain a titanium-containing binder.
[0093] (2) Then, the fumed silica, titanium-containing binder, and field sesbania powder are uniformly mixed in a mass ratio of 1:1:0.1, and stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100°C for 8 hours, and then calcined at 550°C for 6 hours to obtain a cylindrical catalyst precursor.
[0094] (3) The cylindrical catalyst precursor, hexamethyldisilazane and ethylenediamine were mixed in a mass ratio of 1:0.2:0.1, treated at 120°C for 8 hours, washed with ethanol and dried at 100°C for 8 hours to obtain an olefin epoxidation titanium silicon catalyst, which was recorded as S6.
[0095] The UV Raman spectrum of the catalyst S6 is Figure 1 Similarly, 367 cm -1 、496cm -1 、1106cm -1 Spectral peak, 1106cm -1 The peak intensity is 367cm -1 The overall silicon-titanium molar ratio of the catalyst S6 is 44, the surface silicon-titanium molar ratio is 23, and the surface silicon-carbon molar ratio is 3.5; the catalyst S6 is at 20°C, P / P 0 =0.1 and the adsorption time is 2h. The toluene adsorption amount measured is 270 mg / g; the mechanical strength of the catalyst S6 is 52 N / cm.
[0096] [Example 7]
[0097] (1) First, SiO 2 :TiO 2 : Tetrapropylammonium hydroxide: water is 1:0.2:0.4:15. Corresponding amounts of water, tetrapropylammonium hydroxide, tetra-n-butyl titanate and ethyl orthosilicate are uniformly mixed, and then treated at 80°C for 8 hours and then at 150°C for 2 hours to obtain a titanium-containing binder.
[0098] (2) Then, the fumed silica, titanium-containing binder, and field sesbania powder are uniformly mixed in a mass ratio of 1:1.5:0.2, and stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100°C for 8 hours, and then calcined at 550°C for 6 hours to obtain a spherical catalyst precursor.
[0099] (3) The spherical catalyst precursor, hexamethyldisilazane and ethylenediamine were mixed in a mass ratio of 1:0.2:0.1, treated at 120°C for 8 hours, washed with ethanol and dried at 100°C for 8 hours to obtain an olefin epoxidation titanium silicon catalyst, which was recorded as S7.
[0100] The UV Raman spectrum of the catalyst S7 is Figure 1 Similarly, 364 cm -1 , 500cm -1 、1102cm -1 Spectral peak, 1102cm -1 The peak intensity is 364cm -1The overall silicon-titanium molar ratio of the catalyst S7 is 26, the surface silicon-titanium molar ratio is 12, and the surface silicon-carbon molar ratio is 3.4; the catalyst S7 is at 20°C, P / P 0 =0.1 and the adsorption time is 2h. The toluene adsorption amount measured is 312 mg / g; the mechanical strength of the catalyst S7 is 75 N / cm.
[0101] [Example 8]
[0102] (1) First, SiO 2 :TiO 2 : Tetrapropylammonium hydroxide: water is 1:0.2:0.4:15. Corresponding amounts of water, tetrapropylammonium hydroxide, tetra-n-butyl titanate and ethyl orthosilicate are uniformly mixed, and then treated at 80°C for 8 hours and then at 150°C for 2 hours to obtain a titanium-containing binder.
[0103] (2) Then, the fumed silica, titanium-containing binder, and field sesbania powder are uniformly mixed in a mass ratio of 1:0.4:0.01, and stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100°C for 8 hours, and then calcined at 550°C for 6 hours to obtain a cylindrical catalyst precursor.
[0104] (3) The cylindrical catalyst precursor, hexamethyldisilazane and ethylenediamine were mixed in a mass ratio of 1:0.2:0.1, treated at 120°C for 8 hours, washed with ethanol and dried at 100°C for 8 hours to obtain an olefin epoxidation titanium silicon catalyst, which was recorded as S8.
[0105] The UV Raman spectrum of the catalyst S8 is Figure 1 Similarly, 364 cm -1 , 500cm -1 、1102cm -1 Spectral peak, 1102cm -1 The peak intensity is 364cm -1 The overall silicon-titanium molar ratio of the catalyst S8 is 98, the surface silicon-titanium molar ratio is 50, and the surface silicon-carbon molar ratio is 2.5; the catalyst S8 is at 20°C, P / P 0 =0.1 and the adsorption time is 2h. The toluene adsorption amount measured is 320 mg / g; the mechanical strength of the catalyst S8 is 50 N / cm.
[0106] [Example 9]
[0107] (1) First, SiO 2 :TiO 2: Tetrapropylammonium hydroxide: water is 1:0.2:0.4:15. Corresponding amounts of water, tetrapropylammonium hydroxide, tetra-n-butyl titanate and ethyl orthosilicate are uniformly mixed, and then treated at 80°C for 8 hours and then at 150°C for 2 hours to obtain a titanium-containing binder.
[0108] (2) Then, the fumed silica, titanium-containing binder, and field sesbania powder are uniformly mixed in a mass ratio of 1:1:0.1, and stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100°C for 8 hours, and then calcined at 550°C for 6 hours to obtain a cylindrical catalyst precursor.
[0109] (3) The cylindrical catalyst precursor, dimethyldiethoxysilane and n-propylamine were mixed in a mass ratio of 1:0.1:0.5, treated at 120°C for 8 hours, washed with ethanol and dried at 100°C for 8 hours to obtain an olefin epoxidation titanium silicon catalyst, denoted as S9.
[0110] The UV Raman spectrum of the catalyst S9 is Figure 1 Similarly, 364 cm -1 , 500cm -1 、1102cm -1 Spectral peak, 1102cm -1 The peak intensity is 364cm -1 The overall silicon-titanium molar ratio of the catalyst S9 is 32, the surface silicon-titanium molar ratio is 17, and the surface silicon-carbon molar ratio is 6; the catalyst S9 is at 20°C, P / P 0 =0.1 and the adsorption time is 2h. The toluene adsorption amount measured is 150 mg / g; the mechanical strength of the catalyst S9 is 69 N / cm.
[0111] [Example 10]
[0112] (1) First, SiO 2 :TiO 2 : Tetrapropylammonium hydroxide: water is 1:0.2:0.4:15. Corresponding amounts of water, tetrapropylammonium hydroxide, tetra-n-butyl titanate and ethyl orthosilicate are uniformly mixed, and then treated at 80°C for 8 hours and then at 150°C for 2 hours to obtain a titanium-containing binder.
[0113] (2) Then, the fumed silica, titanium-containing binder, and field sesbania powder are uniformly mixed in a mass ratio of 1:1:0.1, and stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100°C for 8 hours, and then calcined at 550°C for 6 hours to obtain a cylindrical catalyst precursor.
[0114] (3) The cylindrical catalyst precursor, octadecyldimethylmethoxysilane and hexamethylenediamine were mixed in a mass ratio of 1:0.02:0.02, treated at 180° C. for 1 hour, washed with ethanol, and dried at 100° C. for 8 hours to obtain an olefin epoxidation titanium silicon catalyst, which was recorded as S10.
[0115] The UV Raman spectrum of the catalyst S10 is Figure 1 Similarly, 364 cm -1 , 500cm -1 、1102cm -1 Spectral peak, 1102cm -1 The peak intensity is 364cm -1 The overall silicon-titanium molar ratio of the catalyst S10 is 43, the surface silicon-titanium molar ratio is 21, and the surface silicon-carbon molar ratio is 0.6; the catalyst S10 is at 20°C, P / P 0 =0.1 and the adsorption time is 2h. The toluene adsorption amount measured is 450 mg / g; the mechanical strength of the catalyst S10 is 55 N / cm.
[0116] [Example 11]
[0117] (1) First, SiO 2 :TiO 2 : Tetrapropylammonium hydroxide: water is 1:0.2:0.4:15. Corresponding amounts of water, tetrapropylammonium hydroxide, tetra-n-butyl titanate and ethyl orthosilicate are uniformly mixed, and then treated at 80°C for 8 hours and then at 150°C for 2 hours to obtain a titanium-containing binder.
[0118] (2) Then, the fumed silica, titanium-containing binder, and field sesbania powder are uniformly mixed in a mass ratio of 1:1:0.1, and stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100°C for 8 hours, and then calcined at 550°C for 6 hours to obtain a cylindrical catalyst precursor.
[0119] (3) The cylindrical catalyst precursor, hexamethyldisilazane and methylamine were mixed in a mass ratio of 1:0.25:0.15, treated at 100°C for 12 hours, washed with ethanol and dried at 100°C for 8 hours to obtain an olefin epoxidation titanium silicon catalyst, which was recorded as S11.
[0120] The UV Raman spectrum of the catalyst S11 is Figure 1 Similarly, 364 cm -1 , 500cm -1 、1102cm -1 Spectral peak, 1102cm -1 The peak intensity is 364cm -1The overall silicon-titanium molar ratio of the catalyst S11 is 36, the surface silicon-titanium molar ratio is 18, and the surface silicon-carbon molar ratio is 1; the catalyst S11 is at 20°C, P / P 0 =0.1 and the adsorption time is 2h. The toluene adsorption amount measured is 400mg / g; the mechanical strength of the catalyst S11 is 52N / cm.
[0121] [Example 12]
[0122] (1) First, SiO 2 :TiO 2 : Tetrapropylammonium hydroxide: water is 1:0.2:0.4:15. Corresponding amounts of water, tetrapropylammonium hydroxide, tetra-n-butyl titanate and ethyl orthosilicate are uniformly mixed, and then treated at 80°C for 8 hours and then at 150°C for 2 hours to obtain a titanium-containing binder.
[0123] (2) Then, the fumed silica, titanium-containing binder, and field sesbania powder are uniformly mixed in a mass ratio of 1:1:0.1, and stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100°C for 8 hours, and then calcined at 550°C for 6 hours to obtain a cylindrical catalyst precursor.
[0124] (3) The cylindrical catalyst precursor, hexamethyldisilazane and ethylenediamine were mixed in a mass ratio of 1:0.15:0.1, treated at 80°C for 24 hours, washed with ethanol and dried at 100°C for 8 hours to obtain an olefin epoxidation titanium silicon catalyst, which was recorded as S12.
[0125] The UV Raman spectrum of the catalyst S12 is Figure 1 Similarly, 364 cm -1 , 500cm -1 、1102cm -1 Spectral peak, 1102cm -1 The peak intensity is 364cm -1 The overall silicon-titanium molar ratio of the catalyst S12 is 37, the surface silicon-titanium molar ratio is 19, and the surface silicon-carbon molar ratio is 5; the catalyst S12 is at 20°C, P / P 0 =0.1 and the adsorption time is 2h, the toluene adsorption amount measured is 200mg / g; the mechanical strength of the catalyst S12 is 62N / cm.
[0126] [Examples 13 to 24]
[0127] The olefin epoxidation titanium silicon catalysts prepared in Examples 1 to 12 were subjected to liquid phase continuous propylene epoxidation in stainless steel fixed bed reaction devices. 3 grams of olefin epoxidation titanium silicon catalysts were crushed into 20-40 mesh particles and filled in a stainless steel reaction tube, and both ends of the reaction tube were filled with glass beads. The reaction was controlled under liquid phase epoxidation conditions, the reaction temperature was 90°C, the reaction pressure was 3.0 MPa, and the mode of lower feeding and upper discharging was adopted. Nitrogen was used to balance the propylene pressure to 3.5 MPa to ensure that the propylene was completely liquefied. The propylene raw material liquid was fed separately, recorded as raw material liquid A; a cumene solution with a mass fraction of 80% of cumene hydroperoxide was selected and mixed with cumene solvent, recorded as raw material liquid B. The two raw material liquids were fed separately by plunger pumps, and the two raw material liquids were premixed before flowing through the catalyst bed. In the total raw material feed flow, the mass fraction of propylene was 20%, the molar ratio of propylene to hydrogen peroxide was 1:0.15, and the flow rate of the total raw material unit mass catalyst was 5 mL·g cat. -1 ·h -1 The reaction liquid after passing through the catalyst bed was collected, and the results are shown in Table 1.
[0128] Table 1 Catalytic propylene epoxidation performance of catalysts in various examples
[0129]
[0130]
[0131] a. The conversion rate and residual rate of cumene hydroperoxide are the data at the beginning of the reaction;
[0132] b. During continuous reaction, the selectivity of propylene oxide and the ratio of main products to by-products remain stable;
[0133] c. Catalyst stabilization time refers to the operation time from the beginning of the reaction to the time when the conversion rate of cumene hydroperoxide is less than 98.0%, that is, the residual rate of cumene hydroperoxide in the reaction solution reaches 2%.
[0134] [Comparative Example 1]
[0135] (1) First, SiO 2 : Tetrapropylammonium hydroxide: water is 1:0.4:15. Corresponding amounts of water, tetrapropylammonium hydroxide and ethyl orthosilicate are uniformly mixed, and then treated at 80°C for 8 hours and then at 150°C for 2 hours to obtain a binder.
[0136] (2) Then, the fumed silica, the binder, and the sesbania powder were mixed evenly in a mass ratio of 1:1:0.1, and stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture was dried at 100°C for 8 hours, and then calcined at 550°C for 6 hours to obtain a cylindrical catalyst precursor.
[0137] (3) The cylindrical catalyst precursor, hexamethyldisilazane and ethylenediamine were mixed in a mass ratio of 1:0.2:0.1, treated at 120°C for 8 hours, washed with ethanol and dried at 100°C for 8 hours to obtain a titanium silicon catalyst, which was recorded as D1.
[0138] The UV Raman spectrum of the catalyst D1 is as follows Figure 2 As shown, 478 cm -1 、615cm -1 、818cm -1 、990cm -1 、1102cm -1 These peaks are attributed to amorphous SiO 2 The catalyst D1 does not contain titanium and has a surface silicon-carbon molar ratio of 2.4; the catalyst D1 is at 20°C, P / P 0 =0.1 and the adsorption time is 2h. The toluene adsorption amount measured is 330 mg / g; the mechanical strength of the catalyst D1 is 65 N / cm.
[0139] [Comparative Example 2]
[0140] (1) First, SiO 2 :TiO 2 Relevant amounts of water, tetrabutyl titanate and ethyl orthosilicate were uniformly mixed in a ratio of 1:0.2:15, and then treated at 80°C for 8 hours and then at 150°C for 2 hours to obtain a titanium-containing binder.
[0141] (2) Then, the fumed silica, titanium-containing binder, and field sesbania powder are uniformly mixed in a mass ratio of 1:1:0.1, and stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100°C for 8 hours, and then calcined at 550°C for 6 hours to obtain a cylindrical catalyst precursor.
[0142] (3) The cylindrical catalyst precursor, hexamethyldisilazane and ethylenediamine were mixed in a mass ratio of 1:0.2:0.1, treated at 120°C for 8 hours, washed with ethanol and dried at 100°C for 8 hours to obtain a titanium silicon catalyst, which was recorded as D2.
[0143] The UV Raman spectrum of the catalyst D2 is as follows Figure 3 As shown, the observed -1 、512cm -1 、628cm -1 These peaks are attributed to TiO 2 The overall silicon-titanium molar ratio of the catalyst D2 is 28, the surface silicon-titanium molar ratio is 13, and the surface silicon-carbon molar ratio is 3.1; the catalyst D2 is at 20°C, P / P0 =0.1 and the adsorption time is 2h. The toluene adsorption amount measured is 292 mg / g; the mechanical strength of the catalyst D2 is 54 N / cm.
[0144] [Comparative Example 3]
[0145] (1) First, SiO 2 :TiO 2 : Tetrapropylammonium hydroxide: water is 1:0.2:0.4:15. Corresponding amounts of water, tetrapropylammonium hydroxide, tetra-n-butyl titanate and ethyl orthosilicate are uniformly mixed to obtain a titanium-containing binder.
[0146] (2) Then, the fumed silica, titanium-containing binder, and field sesbania powder are uniformly mixed in a mass ratio of 1:1:0.1, and stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100°C for 8 hours, and then calcined at 550°C for 6 hours to obtain a cylindrical catalyst precursor.
[0147] (3) The cylindrical catalyst precursor, hexamethyldisilazane and ethylenediamine were mixed in a mass ratio of 1:0.2:0.1, treated at 120°C for 8 hours, washed with ethanol and dried at 100°C for 8 hours to obtain a titanium silicon catalyst, which was recorded as D3.
[0148] The UV Raman spectrum of the catalyst D3 is as follows Figure 4 As shown, 485 cm -1 、1082cm -1 The peaks are attributed to amorphous SiO 2 The catalyst D3 has an overall silicon-titanium molar ratio of 29, a surface silicon-titanium molar ratio of 14, and a surface silicon-carbon molar ratio of 2.9; the catalyst D3 has a temperature of 20°C, P / P 0 =0.1 and the adsorption time is 2h. The toluene adsorption amount measured is 306mg / g; the mechanical strength of the catalyst D3 is 50N / cm.
[0149] [Comparative Example 4]
[0150] (1) First, SiO 2 :TiO 2 : Tetrapropylammonium hydroxide: water is 1:0.2:0.4:15. Corresponding amounts of water, tetrapropylammonium hydroxide, tetra-n-butyl titanate and ethyl orthosilicate are uniformly mixed, and then treated at 80°C for 8 hours and then at 150°C for 24 hours to obtain a titanium-containing binder.
[0151] (2) Then, the fumed silica, titanium-containing binder, and field sesbania powder are uniformly mixed in a mass ratio of 1:1:0.1, and stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100°C for 8 hours, and then calcined at 550°C for 6 hours to obtain a cylindrical catalyst precursor.
[0152] (3) The cylindrical catalyst precursor, hexamethyldisilazane and ethylenediamine were mixed in a mass ratio of 1:0.2:0.1, treated at 120°C for 8 hours, washed with ethanol and dried at 100°C for 8 hours to obtain a titanium silicon catalyst, which was recorded as D4.
[0153] The UV Raman spectrum of the catalyst D4 is as follows Figure 5 As shown, 380 cm -1 、514cm -1 、1125cm -1 Spectral peak, 380cm -1 The peak is attributed to the MFI skeleton, 514 cm -1 、1125cm -1 The peaks belong to the tetracoordinated titanium species in the MFI framework; the overall silicon-titanium molar ratio of the catalyst D4 is 30, the surface silicon-titanium molar ratio is 15, and the surface silicon-carbon molar ratio is 3.2; the catalyst D4 is 20°C, P / P 0 =0.1 and the adsorption time is 2h. The toluene adsorption amount measured is 284 mg / g; the mechanical strength of the catalyst D4 is 42 N / cm.
[0154] [Comparative Example 5]
[0155] (1) First, SiO 2 :TiO 2 : Tetrapropylammonium hydroxide: water is 1:0.2:0.4:15. Corresponding amounts of water, tetrapropylammonium hydroxide, tetra-n-butyl titanate and ethyl orthosilicate are uniformly mixed, and then treated at 80°C for 8 hours and then at 150°C for 2 hours to obtain a titanium-containing binder.
[0156] (2) Then, the fumed silica, titanium-containing binder, and field sesbania powder are uniformly mixed in a mass ratio of 1:1:0.1, and stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100°C for 8 hours, and then calcined at 550°C for 6 hours to obtain a cylindrical catalyst precursor.
[0157] (3) The cylindrical catalyst precursor and hexamethyldisilazane were mixed in a mass ratio of 1:0.2, treated at 120° C. for 8 hours, washed with ethanol, and dried at 100° C. for 8 hours to obtain a titanium silicon catalyst, which was recorded as D5.
[0158] The UV Raman spectrum of the catalyst D5 is as follows Figure 6 As shown, 350 cm -1 、517cm -1 、782cm -1 、1089cm -1 Spectral peak, 350cm -1 、782cm -1 The peak is related to the vibration of Si-O-Si, 517cm -1 、1089cm -1 The peaks are related to the vibration of the tetracoordinated titanium species; the overall silicon-titanium molar ratio of the catalyst D5 is 30, the surface silicon-titanium molar ratio is 14, and the surface silicon-carbon molar ratio is 300; the catalyst D5 is at 20°C, P / P 0 =0.1 and the adsorption time is 2h. The toluene adsorption amount measured is 10 mg / g; the mechanical strength of the catalyst D5 is 68 N / cm.
[0159] [Comparative Example 6]
[0160] (1) First, SiO 2 :TiO 2 : Tetrapropylammonium hydroxide: water is 1:0.2:0.4:15. Corresponding amounts of water, tetrapropylammonium hydroxide, tetra-n-butyl titanate and ethyl orthosilicate are uniformly mixed, and then treated at 80°C for 8 hours and then at 150°C for 2 hours to obtain a titanium-containing binder.
[0161] (2) Then, the fumed silica, titanium-containing binder, and field sesbania powder are uniformly mixed in a mass ratio of 1:1:0.1, and stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100°C for 8 hours, and then calcined at 550°C for 6 hours to obtain a cylindrical catalyst precursor.
[0162] (3) The cylindrical catalyst precursor and ethylenediamine were mixed in a mass ratio of 1:0.1, treated at 120° C. for 8 hours, washed with ethanol, and dried at 100° C. for 8 hours to obtain a titanium silicon catalyst, which was recorded as D6.
[0163] The UV Raman spectrum of the catalyst D6 is as follows Figure 7 As shown, 356 cm -1 、519cm -1 、945cm -1 、1094cm -1 Spectral peak, 356cm -1 The peak is related to the vibration of Si-O-Si, 519cm -1 、945cm -1 、1094cm -1The peaks are related to the vibration of the tetracoordinated titanium species; the overall silicon-titanium molar ratio of the catalyst D6 is 34, the surface silicon-titanium molar ratio is 16, and the surface silicon-carbon molar ratio is 40; the catalyst D6 is at 20°C, P / P 0 =0.1 and the adsorption time is 2h. The toluene adsorption amount measured is 65mg / g; the mechanical strength of the catalyst D6 is 64N / cm.
[0164] [Comparative Example 7]
[0165] (1) First, SiO 2 :TiO 2 : Tetrapropylammonium hydroxide: water is 1:0.2:0.4:15. Corresponding amounts of water, tetrapropylammonium hydroxide, tetra-n-butyl titanate and ethyl orthosilicate are uniformly mixed, and treated at 150° C. for 30 hours to obtain a titanium-containing binder.
[0166] (2) Then, the fumed silica, titanium-containing binder, and field sesbania powder are uniformly mixed in a mass ratio of 1:1:0.1, and stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100°C for 8 hours, and then calcined at 550°C for 6 hours to obtain a cylindrical catalyst precursor.
[0167] (3) The cylindrical catalyst precursor, hexamethyldisilazane and ethylenediamine were mixed in a mass ratio of 1:0.2:0.1, treated at 120°C for 8 hours, washed with ethanol and dried at 100°C for 8 hours to obtain an olefin epoxidation titanium silicon catalyst, which was recorded as D7.
[0168] The UV Raman spectrum of the catalyst D7 is Figure 5 Similarly, 380 cm -1 、515cm -1 、1124cm -1 The overall silicon-titanium molar ratio of the catalyst D7 is 29, the surface silicon-titanium molar ratio is 14, and the surface silicon-carbon molar ratio is 3.1; the catalyst D7 is 20°C, P / P 0 =0.1 and the adsorption time is 2h. The toluene adsorption amount measured is 280 mg / g; the mechanical strength of the catalyst D7 is 45 N / cm.
[0169] [Comparative Examples 8 to 14]
[0170] The titanium silicon catalysts D1 to D7 obtained in Comparative Examples 1 to 7 were subjected to liquid phase continuous epoxidation of propylene according to the reaction conditions of Examples 13 to 24. The reaction results are shown in Table 2 below:
[0171] Table 2 Catalytic performance of propylene epoxidation by catalysts of various comparative examples
[0172]
[0173] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A titanium silicon catalyst for olefin epoxidation, having an ultraviolet Raman spectrum at 364±6cm -1 、500±6cm -1 and 1102±6cm -1 There are spectral peaks at 1102±6cm -1 The intensity of the peak is 364±6cm -1 1.0 to 10.0 times, preferably 3.0 to 8.0 times, the peak intensity.
2. The titanium silicon catalyst according to claim 1, characterized in that: The titanium silicon catalyst comprises silicon, titanium and carbon, and the overall silicon-titanium molar ratio is 20-200, preferably 25-100; and / or the surface silicon-titanium molar ratio is 10-100, preferably 12-50; the surface silicon-carbon molar ratio is 0.5-6.0, preferably 1.0-5.
0.
3. The titanium silicon catalyst according to claim 1, characterized in that: The toluene adsorption amount of the titanium silicon catalyst measured under the conditions of 20° C., P / P0=0.1 and adsorption time of 2 hours is 150-450 mg / g molecular sieve, preferably 250-400 mg / g molecular sieve.
4. The titanium-silicon catalyst according to claim 1, characterized in that: The mechanical strength of the titanium silicon catalyst is 40 to 90 N / cm, preferably 50 to 80 N / cm.
5. A method for preparing an olefin epoxidation titanium silicon catalyst, comprising the following steps: (1) mixing silicon source A, titanium source, organic base and water, and subjecting them to hydrothermal treatment to prepare a titanium-containing binder; (2) kneading the silicon source B, the titanium-containing binder and the pore-forming agent prepared in step (1) into a mold, and calcining the mold to obtain a catalyst precursor; (3) contacting the catalyst precursor of step (2) with a mixture of organic silane and organic amine to obtain the titanium silicon catalyst.
6. The preparation method according to claim 5, characterized in that: The ratio of each material in step (1) is calculated by molar ratio: silicon source A is calculated as SiO2: titanium source is calculated as TiO2: organic base: water = 1: x: y: z; wherein x = 0.01-0.5, y = 0.05-0.5, z = 5-25, preferably: x = 0.05-0.3, y = 0.1-0.4, z = 12-20; And / or, the silicon source A is selected from at least one of tetraethyl orthosilicate, fumed silica, and silica sol; the titanium source is selected from at least one of tetrabutyl titanate, tetraisopropyl titanate, titanium tetrachloride, hexafluorotitanic acid, and ammonium hexafluorotitanate; the organic base is selected from at least one of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, dimethyldiethylammonium hydroxide, dimethyldiisopropylammonium hydroxide, piperidine, and hexamethyleneimine; Preferably, the silicon source A is selected from at least one of tetraethyl orthosilicate and silica sol; the titanium source is selected from at least one of tetrabutyl titanate, tetraisopropyl titanate, and hexafluorotitanic acid; and the organic base is selected from at least one of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, dimethyldiethylammonium hydroxide, and dimethyldiisopropylammonium hydroxide.
7. The preparation method according to claim 5, characterized in that: The hydrothermal treatment in step (1) is carried out in stages; the first stage of the hydrothermal treatment is carried out at 60-119° C. for 1-24 hours, preferably at 80-100° C. for 2-20 hours; the second stage of the hydrothermal treatment is carried out at 120-180° C. for 0.5-6 hours, preferably at 130-170° C. for 2-5 hours; And / or, the temperature of the second stage hydrothermal treatment is 10 to 120°C higher than the temperature of the first stage hydrothermal treatment, preferably 20 to 100°C higher.
8. The preparation method according to claim 5, characterized in that: The ratio of the materials in step (2), the mass ratio of silicon source B in terms of SiO2, titanium-containing binder in step (1), and pore-forming agent is 1:0.2-1.8:0.01-0.3, preferably 1:0.3-1.5:0.05-0.2; And / or, the silicon source B is selected from at least one of fumed silica or silicon powder; the pore-forming agent is selected from at least one of sesbania powder, cellulose, chitosan, lignin, starch, polyethylene glycol, triblock copolymer P123, and F127.
9. The preparation method according to claim 5, characterized in that: The calcination conditions in step (2) are: calcination at 450-650° C. in an oxygen-containing atmosphere for 4-12 hours.
10. The preparation method according to claim 5, characterized in that: In step (3), the mass ratio of the catalyst precursor to the organosilane and the organoamine is 1:0.01-0.5:0.01-0.5, preferably 1:0.05-0.40:0.05-0.40; And / or, the organosilane is selected from at least one of hexamethyldisilazane, triethylchlorosilane, chloromethyl (dimethyl) methoxysilane, octadecyldimethylmethoxysilane, ethoxytrimethylsilane, triallylethoxysilane, dimethyldiethoxysilane, and methylphenyldimethoxysilane, and is preferably at least one of hexamethyldisilazane, triethylchlorosilane, and chloromethyl (dimethyl) methoxysilane; the organic amine is selected from at least one of methylamine, ethylamine, ethylenediamine, n-propylamine, n-butylamine, diethylamine, triethylamine, and hexanediamine, and is preferably at least one of methylamine, ethylamine, ethylenediamine, n-propylamine, n-butylamine, and diethylamine.
11. The preparation method according to claim 5, characterized in that: The treatment conditions in step (3) are: 80-180° C. for 0.5-24 hours, preferably: 100-160° C. for 1-12 hours.
12. The titanium silicon catalyst prepared by the preparation method according to any one of claims 5 to 11.
13. Use of the titanium silicon catalyst according to any one of claims 1 to 4 or the titanium silicon catalyst according to claim 12 in olefin epoxidation reaction.
Citation Information
Patent Citations
Titanium silicalite molecular sieve, preparation method thereof and method for producing ketoxime through macromolecular ketone ammoximation reaction
CN112010321A
Preparation method of titanium-containing catalyst, titanium-containing catalyst and method for preparing epoxy compound
CN114425438A
Whole crystal MWW structure titanium silicalite molecular sieve catalyst and preparation method and application thereof
CN115957808A
Hierarchical pore titanium silicalite molecular sieve, preparation method thereof and method for catalytically oxidizing cyclohexene
CN116332195A
Titanosilicate and method of preparing the same
JP2008050186A
Cited By
Method for preparing 1, 2-epoxyhexane
CN121318882A